Face-Veiled Women in Contemporary Indonesia - Sopyan, Imam (Universitas Islam Internasional Indonesia, 2023)
Eva F. Nisa, Face-Veiled Women in Contemporary Indonesia, Routledge (2023) ; 231 pages + xix)